Experimental and Numerical Modeling of DNAPL Mass Discharge from the Elliptic Pool in Saturated Homogeneous Sandy Soil - Asal Gzar, Hatem; Abdulwahed Hussain, Rasha (International Journal of Engineering and Technology, 2018)
"The present study aims to study the dissolution and mass transport of trichloroethylene (TCE) as Dense Non Aqueous Phase Liquid (DNAPL) in saturated porous media." A rectangular Perspex tank of internal dimensions (150cm length 20cm width and 40 cm height) used to represent the model aquifer. The tank was packed with homogenous soil (Karbala sand)"."Unidirectional flow at five different interstitial velocities (0.9, 1.8, 2.34, 2.7, and 3.6) cm/hr assumed to study the process. The average mass transfer coefficient" was determined for each velocity .Their values were increased with increasing the velocity reaching a limit value" .A conservative tracer is used to obtain the longitudinal and transverse aquifer dispersivities"."An elliptic shape of (TCE) pool was used to carry out the dissolution processes. Steady state dissolved (TCE) concentrations at downstream were collected from ten ports with two different depths under five interstitial velocities". Two linear relationships are created from an elliptic trichloroethylene pool: these relationships were between the average Peclet number in x-direction (Pe*x(e)) with the overall Sherwood number (Sh*(e )), and the other between the average Peclet number in y-direction (Pe*y(e) ) with the overall Sherwood number (Sh*(e))". A numerical modeling was achieved using COMSOL software.